Crisis in Parthia (ca. 90-70/69 BC) and Arsakid Coinages: Preliminary Remarks on Numismatic Evidence - Olbrycht, Marek Jan (Anabasis. Studia Classica et Orientalia, 2019)
The period of over two decades following the close of Mithradates II’s rule (ca. 122-87) and the beginning of the rule of Gotarzes I around 90 is regarded in the literature as a time of deep crisis in the Parthian Empire (ca. 90–70/69). During this time, the issue of the succession to the Arsakid throne turned out to be disputed and fights over the crown took place. There is no uniform record concerning this period of Parthia’s history. Too little attention has been paid so far to the function of the images of a tiara and of a diadem on the Parthian coins from the period ca. 90-70/69. The role of these attributes of royal power was special, and their symbolic function appears to be helpful in solving the mysteries concerning the rulers of Parthia in the first half of the 1st century BC.